Impact of Targeted Local Interventions on Tuberculosis Awareness and Screening Among Persons Experiencing Homelessness During a Large Tuberculosis Outbreak in Atlanta, Georgia, 2015-2016. (July 2020) - Kerr, Eleanor M.; Vonnahme, Laura A.; Goswami, Neela D.
Objectives: Tuberculosis (TB) outbreaks disproportionately affect persons experiencing homelessness (PEH) in the United States. During 2014-2016, a resurgent TB outbreak occurred among PEH in Atlanta, Georgia. To control the outbreak, citywide policies and educational interventions were implemented in January 2015. Policy changes standardized and enforced TB screening requirements for PEH in homeless shelters. Educational campaigns informed PEH of the outbreak and encouraged TB screening. We evaluated factors associated with, and the effect policy changes and educational interventions had on, TB screening and awareness among PEH in Atlanta. Methods: Questions related to TB screening and awareness of the outbreak were added to an annual US Department of Housing and Urban Development survey of PEH in Atlanta in 2015 (n = 296 respondents) and 2016 (n = 1325 respondents). We analyzed the 2016 survey data to determine characteristics associated with outcomes. Results: From 2015 to 2016, reported TB screening increased from 81% to 86%, and awareness of the TB outbreak increased from 68% to 75%. In 2016, sheltered PEH were significantly more likely than unsheltered PEH to report being evaluated for TB in the previous 6 months (prevalence odds ratio [pOR] = 3.18; 95% confidence interval [CI], 2.28-4.47) and to report being aware of the TB outbreak (pOR = 4.00; 95% CI, 2.89-5.55). Conclusions: Implementation of required TB screening and educational interventions may reduce the incidence and severity of TB outbreaks among PEH in other communities. Furthermore, the annual survey of PEH offers an opportunity to collect data to better inform practices and policies.